Beyond the prothrombotic transcript of RPs: alternative splicing and circular RNAs. (10th June 2022) - Bongiovanni, D; Klug, M; Scheibling, E; Tsoy, O; Louadi, Z; Han, J; Laugwitz, KL; Condorelli, G; List, M; Bernlochner, I
Abstract: Funding Acknowledgements: Type of funding sources: Foundation. Main funding source(s): German Center for Cardiovascular Research (DZHK) Background/Introduction: RPs are young, hyper-reactive and RNA-rich platelets. They have a pro-thrombotic potential, are predictors of an insufficient response to antiplatelet therapy after myocardial infarction and are suggested to play a key role in patients with chronic coronary syndrome (CCS) and high on-treatment platelet reactivity. Moreover, RPs are promising novel biomarkers for the prediction of adverse cardiovascular events in different pathological settings. Purpose: We aimed to compare for the first time the transcriptomic profiles of RPs and MPs in CCS patients. Method: Using fluorescent activated cell sorting (FACS), we isolated RPs and MPs based on their RNA content from peripheral blood of 19 CCS patients. After sorting, RNA was extracted and quality, concentration and integrity were assessed with the Tapestation 4200 platform (Agilent). TotalRNA libraries were prepared, multiplexed and sequenced on a NextSeq 500 Illumina platform obtaining 80 to 100 million paired-end reads per sample. RNA-sequencing analysis was performed with R and DESeq2, a cut-off of p <0.005 and a log2fc >1 was applied. Alternative splicing event detection and analysis was performed with MAJIQ. We performed circular RNA (circRNA) analysis using CIRCexplorer. Results: With total RNA-sequencing, we detected 1589 genes differentially expressed with 1100 transcripts upregulated in RPs, while 489 were enriched in MPs (Figure 1 A and B). In particular, transcripts for the collagen receptor GP6 (log2FC 1.12, p=6.89x10-41), thrombin receptor PAR4 (F2RL3, log2FC 1.1, p=3.54*10-21) and Von Willebrand Factor (log2FC 1.2, p value 1.26*10-38) were significantly enriched in RPs. We found an enrichment in MPs of transcript coding for genes involved in RNA processing such as the splicing regulator LUC7L3 (log2FC -1.01, p value 6.65*10-22). We detected several splicing events differentially regulated: an alternative splicing on the transcript GP6 is upregulated in RPs (Figure 1C); by the G-protein GNAQ transcript, one alternative splicing event was found upregulated in RPs, while two others were upregulated in MPs. Additionally, we detected an enrichment of the total level of circular RNAs in MPs compared to RPs (Figure 1E). Nevertheless, several circular RNAs that have not been described before were found enriched in RPs (Figure 1F). Conclusion: This study represents the first transcriptomic profiling of RPs and MPs in patients with CCS and provides for the first time a biological explanation of RPs' hyper-reactivity. The clear upregulation of prothrombotic signaling in RPs could provide and explanation to their hyperactivity and their correlation with cardiovascular events in different pathological settings. Altogether, these findings shed light on a new therapeutic niche in CCS patients. Nonetheless, the detrimental role of RPs in patients with coronary artery disease requires further investigations